Adaptation of the Brain Injury Questionnaire of Sexuality Into Bangla and Initial Findings From a Sample Of Bangladeshi Traumatic Brain Injury Patients (Dhaka University Journal of Biological Sciences, 2022)
Bangladesh is an over populated country with a high incidence of traumaticbrain injury (TBI) for which neuropsychological services are only just emerging.In this context the present study undertook in a culturally sensitive manner totranslate into Bangla (Bengali) the Brain Injury Questionnaire of Sexuality (BIQS)and to present findings from a sample of TBI patients. Standard proceduresincluding back translation for scale adaptation were followed. The Banglaversion of BIQS (BIQS-B) were applied on 30 TBI and 53 healthy sample. Factorand principle component analysis of the BIQS-B yielded three components as inthe original scale explaining 75.3% of the total variance. Reliability is satisfactory,matching that of the English version. The TBI sample scored lower on the BIQS-Bthan did the healthy controls by virtue of not reporting the positive changes insexuality over time that the health controls reported (means of 43.90 vs 52.02, p